The role of herpes simplex virus infection in the etiology of head and neck cancer–a Mendelian randomization study - Yan, Ming; Xiao, Li-yuan; Gosau, Martin; Smeets, Ralf; Feng, Hong-chao; Burg, Simon; Fu, Ling-ling; Friedrich, Reinhard E. (Frontiers in Immunology, 2024)
Introduction: Head and neck cancer (HNC) is a complex disease, and multiple risk factors can lead to its progression. Observational studies indicated that herpes simplex virus (HSV) may be correlated with the risk of HNC. However, the causal effects and direction between them were still unclear.Methods: This study utilized a Mendelian randomization (MR) approach for causality assessment between HSV infection and Head and neck cancer based on the latest public health data and Genome-Wide Association Study (GWAS) data. The causal effects were estimated using IVW, weighted median, and MR-Egger. A reverse MR analysis was subsequently performed. Cochrans Q test, MR-Egger intercept test, leave one out analysis, and the funnel plot were all used in sensitivity analyses.Head and neck cancer (HNC) is a complex disease, and multiple risk factors can lead to its progression.Recent studies have shown a potential correlation between herpes simplex virus (HSV) infection and the risk of HNC.Herein, we probed into the causal relation between HSV infection and HNC using Mendelian randomization analysis.With genetic variants as instrumental variables, we performed a comprehensive analysis to evaluate the impact of HSV on the development of HNC. Collectively, a significant association was noted between HSV infection and increased risk of HNC, providing valuable insights into the etiology of this malignancy. Further in-depth study is needed to validate these findings and elucidate the underpinning mechanisms.Yan]: Results: Genetically predicted higher level of HSV-1 IgG was causally related to HNC (OR=1.0019, 95%CI=1.0003-1.0036, p=0.0186, IVW) and oral and oropharyngeal cancer (OR=1.0018, 95%CI=1.0004-1.0033, p=0.0105, IVW). The reverse MR analysis did not demonstrate a reverse causal relationship between HSV and HNC. However, HSV-2 infection was not causally related to HNC data and oropharyngeal cancer data. Sensitivity analysis was performed and revealed no heterogeneity and horizontal pleiotropy.Conclusions: Collectively, a significant association was noted between HSV infection and increased risk of HNC, providing valuable insights into the etiology of this malignancy. Further in-depth study is needed to validate these findings and elucidate the underpinning mechanisms.